Objectification of Conditional Death Penalty Criteria Under Article 100 of The Criminal Code Perspective Legality And Legal Certainty - Novice Afnan El Fikry; Ali Masyhar; Cahya Wulandari; Muhammad Saifullah; Wahid Anshori (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the regulation of conditional death penalty under Article 100 of Law Number 1 of 2023 concerning the Criminal Code from the perspectives of legality and legal certainty while formulating objective and accountable assessment criteria for sentence commutation. Employing a normative legal research method, the study utilizes statutory and conceptual approaches supported by primary, secondary, and tertiary legal materials. The analysis demonstrates that the introduction of a ten year probation period reflects a significant transformation in Indonesian sentencing policy toward a corrective and rehabilitative orientation. However, the legal concepts of remorse and commendable conduct remain insufficiently defined, creating risks of subjective interpretation and inconsistent application. To address this problem, the study develops objective indicators based on responsibility acceptance, rehabilitation participation, behavioural consistency, institutional compliance, positive correctional engagement, and social adaptation. The study further proposes a multidisciplinary assessment framework involving correctional officers, psychologists, criminologists, legal experts, and an integrated assessment board supported by documentation, verification, periodic review, and written justification mechanisms. These findings indicate that the objectification of evaluative criteria and the institutionalization of accountable assessment procedures strengthen legality, enhance legal certainty, and improve the legitimacy of conditional death penalty implementation within a rule of law based criminal justice system.